INCREASING ECOLOGICAL CULTURE IN THE CONSCIOUSNESS OF STUDENTS AND YOUTH (Bulletin of Innovative Research, 2026)
This article examines the formation of environmental consciousness and culture among students and young people, as well as ways to improve their environmental literacy. It highlights the use of ancient and unique sources, particularly the book Avesta, and the heritage of great scholars in providing environmental education and upbringing to the younger generation